Analysis of Flow and Heat Transfer Characteristics and Multi-Objective Optimization for Sinusoidal PCHE - Qixuan Hu; Zhonglei Fan; Zhe Zhang; Yi Lu (Energies, 2023)
A Printed Circuit Heat Exchanger (PCHE) is a compact heat exchanger with high temperature and pressure resistance and is considered one of the best choices for the recuperators in the Supercritical Carbon dioxide (S-CO2) Brayton cycle. The flow and heat transfer performance of sinusoidal channel PCHE were analyzed and a second-order regression model was established based on the response surface method to improve the performance of the continuous channel PCHE. It was found that reducing the channel diameter, increasing the channel amplitude, and reducing the channel pitch can increase the average value of the heat transfer coefficient and pressure drop per unit length. Moreover, sensitivity coefficient analysis was used to investigate the influence of various structural parameters on flow performance, heat transfer performance, and comprehensive performance. In addition, the structure of the sinusoidal channel PCHE was optimized using a multi-objective genetic algorithm, and three sets of Pareto optimal solutions were obtained. The corresponding optimal channel diameter D, channel amplitude A, and channel pitch Lp were in the range of 1.0–1.7 mm, 2.4–3.0 mm, and 15.1–17.0 mm, respectively, which can provide theoretical basis for the design of PCHE.